2010
DOI: 10.1159/000272066
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Hypoxic Stress in Alveolar Epithelial Cells and Microvascular Endothelial Cells

Abstract: Under hypoxic conditions eukaryotic cells and tissues undergo adaptive responses involving glycolysis, angiogenesis, vasoconstriction and inflammation. The underlying molecular mechanisms are not yet fully elucidated and are most likely cell and tissue specific. In the lung, alveolar epithelial cells and microvascular endothelial cells are highly sensitive to hypoxia and together orchestrate a rapid and sustained adaptive response. We examined the effect of different oxygen tensions on cell viability, glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 51 publications
5
20
0
Order By: Relevance
“…Hypoxia has long been recognized to stimulate ET expression, [6][7][8] and more recently hypoxia-inducible transcription factors (HIFs) have been defined as potent stimuli for induction of the pro-hormone. 6,[9][10][11][12] However, we have recently reported that renal ECE-1 expression is markedly enhanced in diabetic rat kidneys and following the administration of iodinated contrast agents, 13 conditions characterized by elevated plasma and renal ET 14,15 and intensified renal parenchymal hypoxia and HIF expression.…”
mentioning
confidence: 99%
“…Hypoxia has long been recognized to stimulate ET expression, [6][7][8] and more recently hypoxia-inducible transcription factors (HIFs) have been defined as potent stimuli for induction of the pro-hormone. 6,[9][10][11][12] However, we have recently reported that renal ECE-1 expression is markedly enhanced in diabetic rat kidneys and following the administration of iodinated contrast agents, 13 conditions characterized by elevated plasma and renal ET 14,15 and intensified renal parenchymal hypoxia and HIF expression.…”
mentioning
confidence: 99%
“…Thus, in this study, we extend the previous findings by showing a similar protective effect in the skin flap tissues. Vascular endothelial cells are the lining component for all vascular networks, and are sensitive to ischemia [27,28]. HUVECs are regarded as a standard endothelial cell line for analysis of vasoreactive responses to various conditions [8,28].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal oxygen conditions, proline hydroxylation reactions target HIF-1α for proteasomal degradation (Signorelli et al 2010). This reaction requires oxygen so that under low oxygen tensions, degradation is inhibited, and HIF-1 accumulates, translocates to the nucleus, heterodimerizes with ARNT (aka HIF-1α), and commences the transcription of genes through specific hypoxia responsive elements (HRE) (Semenza 2001;Signorelli et al 2010).…”
Section: Hif-1α Pathwaymentioning
confidence: 99%
“…Under normal oxygen conditions, proline hydroxylation reactions target HIF-1α for proteasomal degradation (Signorelli et al 2010). This reaction requires oxygen so that under low oxygen tensions, degradation is inhibited, and HIF-1 accumulates, translocates to the nucleus, heterodimerizes with ARNT (aka HIF-1α), and commences the transcription of genes through specific hypoxia responsive elements (HRE) (Semenza 2001;Signorelli et al 2010). Such genes include those involved in erythropoiesis (e.g., erythropoietin (EPO)), glycolysis [hexokinase 2 (HK2), phosphoglycerate kinase 1 (PGK1), lactate dehydrogenase (LDHA), and glucose transporter 1 (SLC2A1)], and in angiogenesis (vascular endothelial growth factor (VEGFA), endothelin 1 (ET1)) (Hu et al 2003;Schodel et al 2011;Semenza and Wang 1992).…”
Section: Hif-1α Pathwaymentioning
confidence: 99%